2015
DOI: 10.1371/journal.pone.0138025
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transcriptome Analysis of Cotton (Gossypium hirsutum L.) Identifies Candidate Gene Signatures in Response to Aflatoxin Producing Fungus Aspergillus flavus

Abstract: Aflatoxins are toxic and potent carcinogenic metabolites produced from the fungi Aspergillus flavus and A. parasiticus. Aflatoxins can contaminate cottonseed under conducive preharvest and postharvest conditions. United States federal regulations restrict the use of aflatoxin contaminated cottonseed at >20 ppb for animal feed. Several strategies have been proposed for controlling aflatoxin contamination, and much success has been achieved by the application of an atoxigenic strain of A. flavus in cotton, peanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 72 publications
(175 reference statements)
0
63
0
Order By: Relevance
“…Different isoforms of chitinases were induced by infection with both atoxigenic and toxigenic A. flavus in cotton pericarp and seed (Bedre et al 2015). Furthermore, a chitinase A positioned in bin 2.04 was associated with a large aflatoxin reducing QTL, as reported by Hawkins et al (2015).…”
Section: Expression Of Pathogenesis-related Genesmentioning
confidence: 64%
See 3 more Smart Citations
“…Different isoforms of chitinases were induced by infection with both atoxigenic and toxigenic A. flavus in cotton pericarp and seed (Bedre et al 2015). Furthermore, a chitinase A positioned in bin 2.04 was associated with a large aflatoxin reducing QTL, as reported by Hawkins et al (2015).…”
Section: Expression Of Pathogenesis-related Genesmentioning
confidence: 64%
“…This inhibition was correlated with the activity levels of β-1,3-glucanase in the callus and in the culture medium. Bedre and co-workers (2015) reported that two β-1,3-glucanases (BG1 and BG3) were highly induced by an atoxigenic strain of A. flavus on cotton seed, whereas another BG3 transcript was upregulated specifically by the toxigenic strain (Bedre et al 2015). The hydrolytic enzymes β-1,3-glucanase and chitinase, such as PRm3, possess antifungal activity by degrading the fungal cell wall containing chitins ).…”
Section: Expression Of Pathogenesis-related Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…In cotton, inoculated bolls were harvested in a time series after inoculation and subjected to RNA sequencing [25]. Differential expression analysis found an up-regulation of defense-related and antifungal genes in pericarp and seeds in response to Aspergillus [25]. Dolezal et al, 2014 [26] inoculated maize kernels and profiled expression with a maize microarray at four days after infection.…”
Section: Introductionmentioning
confidence: 99%